Nucleotide Sequence and Temporal Expression of a Baculovirus Regulatory Gene - Guarino, Linda A. (1987)
The nucleotide sequence of a trans-activating regulatory gene (IE-1) of the baculovirus Autographa californica nuclear polyhedrosis virus has been determined. This gene encodes a protein of 581 amino acids with a predicted molecular weight of 66,856. A DNA fragment containing the entire coding sequence of IE-1 was inserted downstream of an RNA promoter. Subsequent cell-free transcription and translation directed the synthesis of a single peptide with an apparent molecular weight of 70,000. Quantitative S1 nuclease analysis indicated that IE-1 was maximally synthesized during a 1-h virus adsorption period and that steady-state levels of IE-1 message were maintained during the first 24 h of infection. Northern blot hybridization indicated that several late transcripts which overlap the IE-1 gene were transcribed from both strands. The precise locations of the 5′ and 3′ ends of these overlapping transcripts were mapped using S1 nuclease. The overlapping transcripts were grouped in two transcriptional units. One unit was composed of IE-1 and overlapping γ transcripts which initiated upstream of IE-1 and terminated downstream of IE-1. The other unit, transcribed from the opposite strand, consisted of γ transcripts with coterminal 5′ ends and extended 3′ ends. The shorter, more abundant transcripts in this unit overlapped 30 to 40 bases of IE-1 at the 3′ end, while the longer transcripts overlapped the entire IE-1 gene. Transcription of several early A. californica nuclear polyhedrosis virus genes, in addition to 39K, was shown to be trans-activated by IE-1, indicating that IE-1 may have a central role in the regulation of β-gene expression.